PENGARUH MOTIVASI, LINGKUNGAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Yoga Prihanto; Alwi Suddin; Suprihatmi Sri Wardiningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyze the significance effect of motivation, work environment and work discipline on employee performance. This research was conducted at the Public Broadcasting Institute RRI Surakarta. This type of data used qualitative data and quantitative data. Data sources used primary data sources and secondary data. The study population was 185 employees. The sample was 93 employees with proportional cluster sampling technique. The data collection technique used a questionnaire and literature study. Data analysis techniques used multiple linear regression. The results showed that motivation has a significant effect on employees performance Public Broadcasting Institution RRI Surakarta. The work environment has a significant effect on employees performance Public Broadcasting Institutions RRI Surakarta. Work discipline has a significant effect on employees performance Public Broadcasting Institution RRI Surakarta.